Distortion of marxism in Duong Thu Huong`s Novel without a name and Kim Echlin`s The Disappeared - Ng, Wen Lee; Mani, Manimangai (SciPress, 2014)
In Novel Without A Name (1996) and The Disappeared (2010), the brutalities of the Vietnam War and the Cambodian Civil War are depicted vividly. The implementation of suspect Marxist doctrines and ideologies is portrayed as the main factor that led to such atrocities. Thus, the central issue or theme of these two novels is the distortion of Marxism. This is foregrounded not only through incidents that take place on the battlefield, but also through the relationships between characters. The latter are not much explored by scholars to examine the main theme, the distortion of Marxism. Hence, this study investigates the importance of relationships in reflecting and developing the theme, the distortion of Marxism, as depicted in Duong Thu Huong’s Novel Without A Name and Kim Echlin’s The Disappeared via the concept of Marxism. By referring to the true set of Marxist ideologies, the distorted Marxist doctrines implemented in the Marxist regime depicted are shown. This paper reveals that the distortion of Marxist doctrines has a negative impact on the relationships depicted in Novel Without A Name and The Disappeared. There are three main types of relationship portrayed in the novel, namely love, siblings and friendship. All these relationships reflect the theme of both novels, the distortion of Marxism, because all of them are broken or severed at the end of the novels due to the distorted Marxist ideologies and doctrines implemented in the regimes depicted.